Biomechanical report for the IAAF World Championships London 2017 javelin throw women's - Bennett, T.; Walker, J.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s javelin final took place on the evening of August 8th. Coming into the final, Sara Kolak of Croatia was a favourite for the gold medal following a strong season, in which she produced both a personal best and world leading distance of 68.43 m. However, in the second it was Barbora Špotáková, a double Olympic gold medallist and current world record holder from the Czech Republic, who delivered the gold medal throw with a distance of 66.76 m. In the third round Lingwei Li from China provided the main challenge to Špotáková with a throw of 66.25 m (a personal best) for the silver medal. Huihui Lyu produced a best throw of 65.26 m in the fifth round, which was sufficient to secure the bronze medal. (Attention! registration on the IAAF site is required for downloading)